Ethnoveterinary practices for treating parasitic diseases in domestic animals among Kyrgyz farmers - Aldayarov, Nurbek; Tulobaev, Askarbek; Madumarov, Akram; Risvanli, Ali (Elsevier, 2025)
While modern veterinary medicine offers effective treatments, traditional ethnoveterinary practices persist among many farming communities, reflecting centuries-old knowledge and cultural beliefs. This study aimed to document ethnoveterinary remedies and their methods of preparation and application, for treating various parasitic diseases in domestic animals used by Kyrgyz farmers. Data on plant, animal and mineral-based remedies, as well as chemicals used for these purposes, were collected through interviews with 173 dialogue partners (DPs). A total of 3403 use reports (URs) were recorded, indicating 1866 plant-based remedies (2114 URs; 62.1 %), 11 animal-based remedies (693 URs; 20.4 %), 4 mineral-based remedies (236 URs; 6.9 %) and 6 chemicals (360 URs; 10.6 %) used as antiparasitic agents by Kyrgyz farmers. The preparation of 991 homemade single species herbal remedy reports (HSHRs) and 875 homemade mixed species herbal remedy reports (HMHRs) involves the utilisation of 56 plant species belonging to 20 families. Helminthiasis was the most frequently mentioned by DPs (1697 URs; 49.9 %), followed by mange (965 URs; 28.6 %), external parasites (594 URs; 17.4 %) and myiasis (maggots in wounds) (89 URs; 2.6 %), other myiasis (58 URs; 1.7 %). The highest number of URs was observed for cattle (1221 URs; 35.9 %), sheep (733 URs; 21.5 %) and horses (696 URs; 20.4 %), followed by goats (299 URs; 8.8 %), dogs (201 URs; 5.9 %), donkeys (170 URs; 5 %), chickens (59 URs; 1.7 %) and turkeys (24 URs; 0.7 %). All the remedies presented have significance for local residents, who previously had exclusive access to these skills. However, many of the documented remedies require confirmation using modern technologies.
Keywords: Ethnoveterinary; Domestic animals; Parasitic diseases; Homemade remedies; Kyrgyz farmers